IMPLEMENTATION OF PROBLEM BASED LEARNING TO IMPROVE LEARNING OUTCOMES OF BODY ELECTRICAL SYSTEMS IN VOCATIONAL SCHOOLS (ATIKANOTO: Journal of Automotive Engineering Education, 2024)
This research is the application of problem-based learning to improve the study results of the body electrical system, the lighting system material is a quantitative research of the Nonequivalent control group design experiment model carried out at SMK Negeri 1 Purwakarta, this research aims to improve the study result of students reviewed from the cognitive aspect, data collection is carried out by providing pre-tests to students, then given treatment using Problem based learning, then given a post-test at the end of learning. The results showed that the study results of the experiment class showed an increase in study results in 11 students in the "high" category and 22 students in the "medium" category with an average post-test score of 82, The average increase in study resultss in the experiment class was 0.60. Based on observations made by subject teachers, student activities in the experimental class using problem-based learning reached a percentage of 93.7% or in the "very active" category.   Penelitian ini merupakan penerapan problem based learning untuk meningkatkan hasil belajar sistem kelistrikan bodi, materi sistem penerangan merupakan penelitian kuantitatif model eksperimen desain Nonequivalent control group yang dilaksanakan di SMK Negeri 1 Purwakarta, penelitian ini bertujuan untuk meningkatkan hasil belajar peserta didik ditinjau dari aspek kognitif, pengumpulan data dilaksanakan dengan memberikan pre-test kepada peserta didik, kemudian diberikan treatment menggunakan problem based learning, lalu diberikan post-test pada akhir pembelajaran. Hasil penelitian menunjukkan bahwa hasil belajar kelas eksperimen terdapat peningkatan hasil belajar pada 11 peserta didik  kategori “tinggi” dan 22 peserta didik kategori “sedang” dengan nilai rata-rata nilai post-test sebesar 82, Rata-rata peningkatan hasil belajar kelas eksperimen sebesar 0,60. Berdasarkan pengamatan yang dilakukan oleh guru mata pelajaran aktivitas peserta didik pada kelas eksperimen yang menggunakan problem based learning mencapai persentase 93,7% atau dalam kategori “sangat aktif”